Facilitators and Barriers for a Good Night’s Sleep Among Adolescents - Hedin, Gita; Norell-Clarke, Annika; Hagell, Peter; Tønnesen, Hanne; Westergren, Albert; Garmy, Pernilla (Frontiers in Neuroscience, 2020)
Background: Sleep deprivation among adolescents is a major public health issue. Although previous studies have described their sleep habits and the consequences thereof, the voices of adolescents themselves are rarely heard. The aim of this study was to investigate adolescents’ experiences regarding what they perceived as facilitators and barriers for a good night’s sleep. Methods: A qualitative focus group study with Swedish adolescents (n=45) aged 16-18 years was performed with seven focus groups and analyzed using qualitative content analysis. Results: Three categories were identified in the analysis regarding facilitators and barriers for achieving a good night’s sleep: (1) Striving for a sense of well-being, (2) Tiring yourself out, and (3) Regulating electronic media availability. The adolescents thought that sleep was important in order to be able to cope with everyday life and to allow physical recovery. Overall, the adolescents were knowledgeable regarding commonly recommended strategies for improving sleep, but they had trouble finding a balance between sleep and other activities. Electronic media was used to obtain a sense of belonging and to communicate with others, which in itself was described as important for the adolescents’ well-being. However, communicating with friends and family during the night conflicted with achieving a good night’s sleep. Parental behaviors (late work habits, internet rules) were also perceived as important for adolescents’ sleep habits. Conclusions: An understanding of the dilemma of finding a balance between sleep and other activities may aid future sleep-promoting interventions for adolescents, incorporating the impact from social factors’ on the adolescents’ sleep. Keyword: Adolescents; electronic media use; focus group interviews; health; sleep; qualitative content analysis.